Oxygen exchange profile in rat muscles of contrasting fibre types - Behnke, Brad J (Blackwell Science Inc, 2003)
To determine whether fibre type affects the O(2) exchange characteristics of skeletal muscle at the microcirculatory level we tested the hypothesis that, following the onset of contractions, muscle comprising predominately type I fibres (soleus, Sol, 86 % type I) would, based on demonstrated blood flow responses, exhibit a blunted microvascular P(O(2)) (P(O(2),m), which is determined by the O(2) delivery ([Image: see text]) to O(2) uptake ([Image: see text]) ratio) profile (assessed via phosphorescence quenching) compared to muscle of primarily type II fibres (peroneal, Per, 84 % type II). P(O(2),m) was measured at rest, and following the rest-contractions (twitch, 1 Hz, 2–4 V for 120 s) transition in Sol (n = 6) and Per (n = 6) muscles of Sprague-Dawley rats. Both muscles exhibited a delay followed by a mono-exponential decrease in P(O(2),m) to the steady state. However, compared with Sol, Per demonstrated (1) a larger change in baseline minus steady state contracting P(O(2),m) (ΔP(O(2),m)) (Per, 13.4 ± 1.7 mmHg; Sol, 8.6 ± 0.9 mmHg, P < 0.05); (2) a faster mean response time (i.e. time delay (TD) plus time constant (τ); Per, 23.8 ± 1.5 s; Sol, 39.6 ± 4.3 s, P < 0.05); and therefore (3) a greater rate of P(O(2),m) decline (ΔP(O(2),m)/τ; Per, 0.92 ± 0.08 mmHg s(−1); Sol, 0.42 ± 0.05 mmHg s(−1), P < 0.05). These data demonstrate an increased microvascular pressure head of O(2) at any given point after the initial time delay for Sol versus Per following the onset of contractions that is probably due to faster [Image: see text] dynamics relative to those of [Image: see text].